Use Coupon: CART20 and get 20% off on all online Study Material

Total Price: R

There are no items in this cart.
Continue Shopping
Get instant 20% OFF on Online Material.
coupon code: MOB20 | View Course list

Get extra R 150 off

				   prove that:sinAcosB+cosAsinB=sin(A+B)sin(A-B)

6 years ago


Answers : (1)


Dear kiran,

Given the functions (sinα, cosα, sinβ and cos β), we seek a formula that expresses sin(α+β).

ABC which has an angle α
ACD which  "   "    "  β
The long side ("hypotenuse') of ACD is AD=R. Therefore

DC = R sin β
AC = R cos β

BC = AC sin α = R cos β sin α
AB = AC cos α = R cos β cos α

The triangle ADF is right-angled and has the angle (α+β). Therefore

R sin (α+β) = DF
R cos (α+β) = AF

Start by deriving the sine:
R sin (α+β) = DF  =  EF + DE  =  BC + DE

 Note in the drawing the two head-to-head angles marked with double lines: like all such angles, they must be equal. Each of them is one of the two sharp ("acute") angles in its own right-angled triangle. Since the sharp angles in such a triangle add up to 90 degrees, the other two sharp angles must be equal. This justifies marking the angle near D as α, as drawn in the figure.
In the right-angled triangle CED

DE = DC cos α = R sin β cos α
EC = DC sin α = R sin β sin α
Earlier it was already shown that
BC = R cos β sin α
AB = R cos β cos α
R sin (α+β)  =  BC+DE  =  R cos β sin α + R sin β cos α

Cancelling R we have

  sin (α+β)  =  sin α cos β  + cos α sin β


We are all IITians and here to help you in your IIT JEE preparation.

All the best.

 If you like this answer please approve it....

win exciting gifts by answering the questions on Discussion Forum


Sagar Singh

B.Tech IIT Delhi

6 years ago

Post Your Answer

Other Related Questions on Trigonometry

if sinx + sin 2 x+ sin 3 x = 1 , then prove that cos 6 x- 4cos 4 x + 8cos 2 x= 4 .This is the hardest question and I ...
Sin(x) +sin^3(x) = 1-sin^2(x) => sin^2(x)[1+sin^2(x)]^2=cos^4(x)=> [1-cos^2(x)][2-cos^2(x)]^2=cos^4(x)Cos^6(x) - 4cos^4(x) + 8cos^2(x) = 4
kanha kasniya one month ago
Simplify the equation :(cosec a+cot a)(1-cos a). i want the answer immediately please......
(cosec a+cot a)(1-cos a) = cosec a-cosec a*cos a+cot a-cot a*cos a =1/sin a-(cos a)/sin a+(cos a-cos^2 a)/sin a =(1-cos a+cos a-cos^2 a)/sin a =(1-cos^2 a)/sin a =sin^2 a/sin a = sin a
Shreyash Rane one month ago
Find out the value of cot6°× cot66°× cot42°× cot78° such as the given value is equal to 1.
Here use the identities, sinA*sin(A+60)*sin(60-A) = sin(3A)/4 and cosA*cos(A+60)*cos(60-A) = cos(3A)/4 Now divide the costerms eqn with sin terms to form the cot relation. therefore,...
Vikas TU 2 months ago
sir moje illustration 1 samaj nhi a rha pls hlp me AOI ke basic concept bale page pr
@ vishal kindly tell me the full ques or the concept name in which u have problem . be little specific , i am not able to understand your query . else ,u can also attach the perticular ques ...
Umakant biswal 8 days ago
Find the Laplace transform of : t(1+sint) ½ ​....................
Given that t*(sin t )^(1/2) = 2^(1/2)*t* cos(pi/4-t/2) which laplace transformation is which is solved by the matlab software.
Kumar one month ago
View all Questions »

  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details
Get extra R 3,750 off

Get extra R 150 off

More Questions On Trigonometry

Ask Experts

Have any Question? Ask Experts

Post Question

Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details